Current state and development prospects of mining metallurgical complex of Kazakhstan (Journal of Geography and Environmental Management, 2017)
The article is devoted to the design and development strategy mining, state mining and metallurgical complex of the country. The analysis of the current state of mineral resource base of Kazakhstan, some of the results of which are given with the use of materials «Service analysis of the results of subsoil use «Kazgeoinform», publications of geologists and miners of Kazakhstan. Mineral-raw material complex of Kazakhstan is the basis of socio-economic development of Kazakhstan and remains one of the most attractive areas for investment. Only in the last thirteen years the annual volume of investment in the mining of various minerals has increased more than five times. However, a number of them already today there is a lack of replenishment of the resource base, and this threatens the stable development of the extractive industries of the national economy.Kazakhstan industry development Institute, The Committee of Geology and subsoil use Ministry of industry and new technologies of Kazakhstan, a number of institutions conducted an analysis of the state of subsoil use in the Republic of, with the aim of promoting the industrial-innovative development of the country through information and analytical support, aimed at stimulating the development of priority sectors of the economy, ensuring of ecological safety of development of mineral resources.
Keywords: The mineral resources; mining; innovative development; minerals; reserves; investment; mining and metallurgical complexes; environmental problems